PATHOGENETIC MECHANISMS OF MIGRAINE DEVELOPMENT ASSOCIATED WITH HOMOCYSTEINE - Kambarova, Dildora; Usmanova, Durdona (Medical science of Uzbekistan, 2023)
The article studies various mechanisms of the influence of homocysteine ​​in the development of migraine. Homocysteine, a sulfur-containing molecule, is now recognized as an independent risk factor for various thrombotic diseases, especially coronary heart disease and stroke. This article is aimed at providing various mechanisms of development and association of migraine with homocysteine, which will allow in choosing the right treatment tactics.